LABOR MIGRATION AND ECONOMIC AND SOCIAL FACTORS AFFECTING IT - Bobomurodova, Sabrina Ne’matovna; Boliyeva , Madina Farxodovna (INTERNATIONAL CONFERENCES, 2023)
This article analyses the official and unofficial forms of labor migration, their seasonal, temporary and repetitive characteristics, as well as the influence of economic, social and demographic factors affecting migration by the example of some regions of the republic.